CLARIFICATION OF PROTEIN SUB UNIT PILI AND OUTER MEMBRANE PROTEIN ( Omp ) Shigella flexneri AS ADHESION PROTEIN WITH HEM AGGLUTINATION TEST - Fitrianingsih, Avin Ainur (Proceedings of the International Conference on Green Technology; Vol 6 No 1 (2015): Proceeding of International Conference on Green Technology, 2020)
Diarrhea is a serious problem  in developing countries. Shigella flexneri is the commonest cause bacillary diarrhea in developing countries. Vaccination against bacteria Shigella spp. necessary to reduce the incidence of diarrhea bacillary including those caused by S. flexneri. This study aims to explore the hemagglutinin protein (a protein that is able to agglutinate erythrocytes) pili and Omp S. flexneri alleged role in the adhesion of bacteria to the enterocytes. This study using hemagglutination assay method by reacting antigen derived either from protein sub units pili or subunits Omp S. flexneri result of purification, then observed agglutination occurs. At the protein sub units of S. flexneri pili showed: the molecular weight (MW)  72 kDa protein occurs in the agglutination titer 1/4, on the MW  27 kDa agglutination titer 1/16, and the MW 18 kDa occurred agglutination in titers of 1/128. While the Omp protein 72 kDa subunit; 27 kDa; and 18 kDa occurred agglutination in titers of 1/128. These results prove that the pili and Omp protein purification results thought to contain adhesion protein that is able to bind erythrocytes or called hemagglutinin protein. The occurrence of agglutination indicated by the absence of erythrocyte sediment at the bottom of the wells. While the deposition that occurs on the bottom of the well indicates a negative result, this is because the erythrocytes are not bound by a protein sub unit of pili and Omp S. flexneri.